THE PERCEPTION ON THE USE SOCIAL MEDIA IN LEARNING ENGLISH - Rahmawati Dwi Handayani; Muh Syafei Syafei; Aisyah Ririn Perwikasih Utari (Universitas Muria Kudus, 2021)
Abstract The objective of the research to know the perception of fourth semester students of Universitas Muria Kudus on the use social media in learning English. The researcher used descriptive qualitative research and the data was collected by the used of questionnaire. The participants are 50 students of English Education Department of Universitas Muria Kudus. The result showed social media have good perception for the fourth semester students of English Education Department of Universitas Muria Kudus. Social media have provide rich resource to learn English. It is indicate that social media has positive contribution for learning English they are listening, reading, writing and speaking skill.